Assessment of New York City Urgent Care Centers' Emergency Preparedness and Infection Prevention and Control Practices, 2016–2017. (5th June 2022) - Jacobs-Wingo, Jasmine; Beatty, Norman L; Jang, Kristine; Foote, Mary MK
Abstract: Background: Urgent care centers (UCCs) have become frontline healthcare facilities for individuals with acute infectious diseases. Additionally, UCCs could potentially support the healthcare system response during a public health emergency. Investigators sought to assess NYC UCCs' implementation of nationally-recommended IPC and EP practices. Methods: Investigators identified 199 eligible UCCs based on criteria defined by the Urgent Care Association of America. Multiple facilities under the same ownership were considered a network. As part of a cross-sectional analysis, an electronic survey was sent to UCC representatives assessing their respective facilities' IPC and EP practices. Representatives of urgent care networks responded on behalf of all UCCs within the network if all sites within the network used the same policies and procedures. Results: Of the respondents, 18 representing 144 UCCs completed the survey. Of these, 8 of them (44.4% of the respondents) represented more than 1 facility that utilized standardized practices (range = 2-60 facilities). Overall, 81.3% have written IPC policies, 75.0% have EP policies, 80.6% require staff to train on IPC, and 75.7% train staff on EP. Conclusion: Most UCCs reported implementation of IPC and EP practices; however, the comprehensiveness of these activities varied across UCCs. Public health can better prepare the healthcare system by engaging UCCs in planning and executing of IPC and EP-related initiatives.